ANATOMY OF THE CLADODES AND ECOLOGICAL ADAPTATION IN OPUNTIA (CACTACEAE) FROM THE PROVINCE OF BUENOS AIRES (ARGENTINA) (Boletín de la Sociedad Argentina de Botánica, 2018)
In this paper we examine the cladodes anatomy of Opuntia arechavaletae, O. aurantiaca, O. bonaerensis, O. elata, O. ficus-indica, O. megapotamica, O. penicilligera, O. sulphurea var. pampeana, and O. ventanensis that grows in the province of Buenos Aires, Argentina. The aim of this study was to establish diagnostic features in order to deepen knowledge of ability of adaptation to the environmental. Fresh and herbarium samples were prepared according to usual methods for light microscope. Histochemical techniques were performed to identify starch, mucilage and oxalate salts. The main traits found were: epidermis smooth and uniseriate, covered by a thin cuticle and epicuticular waxes; large stomata in low density, located at level with a deep substomatal chamber; a multilayered collenchyma including crystal layer; water storage parenchyma, and in vascular bundles a special water-storage cell type, resistant to collapse, and perhaps having some water transfer function  we named ‘intermediate cells’ which form masses in the xylem of  O. megapotamica, O. penicilligera, O. sulphurea var. pampeana, and O. ventanensis, which grows in xeric, saline and stone soils.